SISTEM PENDUKUNG KEPUTUSAN MEMILIH MEDIA PROMOSI EFEKTIF PADA SMA N 1 BANYUMAS MENGGUNAKAN METODE ANALITYCHAL HIERARCHY PROCESS - Idris, Muhammad; Artina, Bekti (JELTec (Journal of Learning Technology), 2023)
Promotion is an important factor in increasing competitiveness and attracting prospective students at SMA N 1 Banyumas. However, selecting effective promotional media is still a challenge for schools because the various media options available have their own advantages and disadvantages. Therefore, a decision support system (DSS) is needed that can help schools determine the most effective promotional media based on various relevant criteria. This study aims to build a decision support system in selecting effective promotional media at SMA N 1 Banyumas using the Analytical Hierarchy Process (AHP) method. The AHP method is used to analyze and determine the weight of importance of each criterion that influences the selection of promotional media, such as audience reach, cost, effectiveness of information delivery, and level of interaction with prospective students. The results of the study indicate that the developed system is able to provide optimal promotional media recommendations based on the calculation of the priority weight of each alternative analyzed. The implementation of this system is expected to help schools make more objective and strategic decisions in determining the most effective promotional media.